Comparison of the Effects of Utilizing Single and Mixed Freshwater Cyanobacterial Isolates for Landfill Leachate Treatment - W R W A Razak; A Y Daud; A A Aziz; N J Sidik; R Rasol (Geography, Earth Science and Environment: Research Highlights Vol. 4, 2025)
Landfill leachate is the liquid produced from the percolation of rainwater through the decomposed solid waste and the existing water in the waste itself in a landfill. The increasing volume of waste disposal and improper management of landfills have been contributing to the heavily polluted leachate. This study was focused on the investigation of the level of selected parameters in the leachate from Jeram Sanitary Landfill, Selangor, and compared the changes of leachate content before and after treatment by single and mixed cyanobacterial isolates so that the discharge standards can be met. There were two cyanobacterial species used in this study. All the data recorded were analyzed for any significant differences between treatments which are the leachate treatment using single and mixed cultures of cyanobacteria with one-way ANOVA using a statistical software known as Statistical Program for Social Science (SPSS). Local freshwater cyanobacteria were identified based on the polyphasic approach combining morphological and molecular identification using the 16 S rRNA gene sequencing method. The local cyanobacteria isolate (A1) was identified as the genus Cyanobacterium of the order Chroococcales. The A1 isolate together with identified cyanobacteria, Anabaena sp. was used to observe their effectiveness in remediating leachate pollution either as monoculture or in mixed culture. Before the phycoremediation, the characterization of leachate had been carried out. The biological oxygen demand (BOD5) , chemical oxygen demand (COD), pH value, the concentration of ammonia-nitrogen (NH3 - N), nitrite (\(NO_2^-\)) and nitrate (\(NO_3^-\)) of the raw leachate determined were 22.37mg/L,58.33mg/L,7.84,82.7mg/L,88.67mg/L and 89.43mg/L, respectively. Using a single Anabaena sp . demonstrates the most effective method of removing all contaminants in the leachate. The removal of COD was the highest at 105.71% followed by BOD5 at 92.71% and (\(NO_3^-\)) at 82.09%. This finding suggested that to achieve the optimum removal of BOD5 COD, NH3 - N, NO2 - and NO3 - content in leachate sample, treatment by Anabaena sp. should be applied. The findings from this study, may be an addition to the alternatives for leachate treatment especially for the application of Anabaena sp.